OBSERVATION ON THE NEST CHARACTERISTICS, CLUTCH SIZE AND HATCHING RATE OF PIED STILT (Himantopus leucocephalus) AND JAVAN PLOVER (Anarhynchus javanicus) IN WONOREJO FISHPOND, EAST JAVA, INDONESIA - Nurul Husna Siregar; Dyah Perwitasari-Farajallah; Yeni Aryati Mulyani (BRIN Publishing (Penerbit BRIN), 2025)
Knowledge of breeding by the Pied Stilt (Himantopus leucocephalus) and Javan Plover (Anarhynchus javanicus) is limited. During fieldwork from 15 August to 10 November 2015 we studied nest features, hatching rate and clutch size of both species at the Wonorejo Fishpond in East Java, Indonesia. During the investigation 42 Pied Stilt nests and 27 Javan Plover nests were found. Pied Stilts build their nests in both mud and surrounded by water; the mud nests include a greater variety of components than nests on water. We provide the first description of the nest of Javan Plover nest on the ground and are made of wood, snail shells and shellfish. The Pied Stilt's clutch size is typically 2-4 eggs, while the Javan Plover's clutch size is often 2-3 eggs. The hatching rate of Javan Plover was 61.5%, and 75% in Pied Stilt with flooding the key factor influencing hatching rate.